Factors Affecting Social Behavior of an Individual- Partial Least Square- Structural Equation Modelling - Sinha, Arpan; Bagga, Teena; Kumar Yadav, Rajesh; Pathak, Priyanshi (International Journal of Psychosocial Rehabilitation, 2020)
This study is focused on the Social Behavior of an individual and the various factors that affect it both positively and negatively. This research was conducted with a sample of 456 employees from the Manufacturing and Service sector in Delhi NCR. The reliability of the data was checked through Composite Reliability values and Cronbach’s Alpha values. The collected data was then analyzed using MS Excel, SPSS and Smart PLS software. Partial Least Squares- Structured Equation Modeling was used to analyze the factors affecting Social Behavior. Upon analyzes it was found that some factors had positive impact on the Social Behavior of a person and some did not. The entire proposed hypotheses were supported except the effect of Organization Culture on Social Behavior. On the basis of findings of the study managerial implications have been discussed in the manuscript. The results and discussions of the current work may also provide meaningful implications for further research.